조화로운 바다 내비게이션 서비스 운영을 위한 제언: 부산항 부근 구역을 중심으로 - 박상원; 이수; 박민정; 박영수 (한국해양경찰학회보, 11(2), 2021)
IMO(국제해사기구)는 2014년 e-Navigation 전략이행계획을 승인하였다. 우리나라는 정부 주도로 IMO의 e-Navigation 개념에서 Non-SOLAS 선박 대상 서비스를 추가하여 한국형 e-Navigation 서비스를 개발하였다. 그리고 2021년부터 정부는 세계 최초로 바다 내비게이션 서비스를 시행할 예정이다. 본 논문은 서비스 시행에 앞서 관련법과 규정을 분석하여 서비스의 조화로운 운영을 위한 제언을 하고자 하였다. 이를 위해 서비스 시범구역이며, 선박 입·출항이 가장 많은 부산 부근 해역을 대상으로 해상교통 조사를 통한 해상교통 현황, 최근 5년간 해양사고 조사, 선박 입·출항현황 및 관련법과 정책을 분석하였다. 그 결과 바다 내비게이션 서비스의 조화로운 운영을 위한 바다 내비게이션 센터와 VTS(해상교통관제) 센터 간 정보연계를 통해 선박운항자 대상 안전정보의 일원화, 서비스 활용 가이드라인 개발, 적극적인 서비스 제공으로 VTS 관리 사각지대 관리방안 수립, 단말기의 효율적인 활용을 위한 교육 프로그램 개발 등 4가지 사항을 제안하였다. 본 연구를 바탕으로 바다 내비게이션 서비스와 기존 서비스 간 조화로운 운영을 통해, 감시 사각지대 없는 안전해역 관리시스템이 구축되길 기대한다. The International Maritime Organization (IMO) approved the e-Navigation Strategy Implementation Plan. Korea developed the Korean e-Navigation service by adding Non-SOLAS vessel target service in IMO's e-Navigation concept. And from 2021, the government will implement the world's first sea navigation service. The purpose of this study is to analyze the relevant laws and regulations prior to the implementation of the service and to make suggestions for the harmonious operation of the service. Therefore we analyzed the maritime traffic status through maritime traffic survey, maritime accident survey over the past 5 years, ship entry/departure status, and related laws and policies in the area near Busan, which is a service demonstration area and has the largest number of ships entering and departing. For the harmonious operation of the current marine traffic environment and sea navigation services, four things were proposed: connection with VTS Center, development of service utilization guidelines, the establishment of management blind sector management measures, and development of education programs. Based on this study, it is hoped that a safe sea area management system will be established through harmonious operation between sea navigation services and existing services. KCI Citation Count: 0